2016
DOI: 10.1021/acs.energyfuels.5b02634
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study on the Process of Cyclopentane + Methane Hydrate Formation in NaCl Solution

Abstract: In this work, the formation kinetics of cyclopentane (CP) + methane hydrate is studied. CP is used as a promoter to accelerate the hydrate formation. The total methane consumption, the induction time, and the formation rate were investigated under different hydrate formation conditions in NaCl solution. The results indicated that the pressure driving force could increase the gas consumption and shorten the induction time. Meanwhile, the induction time could be greatly influenced by the pressure driving force a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…During further growth of the hydrate, the CO 2 gas diffused into the inside surface of the shell and water diffused to the outer surface of shell . More vigorous stirring could promote CO 2 gas dissolution and dispersion into the solution and enhance the mass transfer rate . According to Sloan, the collision of a hydrate particle with another water droplet could seed hydrate growth in the droplet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During further growth of the hydrate, the CO 2 gas diffused into the inside surface of the shell and water diffused to the outer surface of shell . More vigorous stirring could promote CO 2 gas dissolution and dispersion into the solution and enhance the mass transfer rate . According to Sloan, the collision of a hydrate particle with another water droplet could seed hydrate growth in the droplet.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have studied the hydrate induction time for gases in pure water. ,,,, The main influencing factors are subcooling, driving force, memory effect, stirring rate, and gas composition. , However, hydrate formation in crude oil or in water-in-oil emulsion may not be the same as the process in pure water, as for example there will be differences in the heat and mass transfer. So it is essential to study the hydrate induction time in water-in-oil emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison of three different cyclopentane derivatives on CO 2 hydrate formation examined by Hong et al, cyclopentane had a milder phase equilibrium condition in 3.5 wt % NaCl solution compared to cyclopentanone and cyclopentanol . The positive influence of cyclopentane on the rate of CH 4 hydrate in the presence of 3.5 wt % NaCl was shown by Lv and co-workers . The hydrate dissociation condition of (CO 2 + cyclopentane) in the electrolyte aqueous solution of NaCl (up to 20 wt %) was reported by Ngema et al They found that NaCl shifts the thermodynamic condition of hydrate formation to lower temperatures and higher pressures.…”
Section: Introductionmentioning
confidence: 83%
“…33 The positive influence of cyclopentane on the rate of CH 4 hydrate in the presence of 3.5 wt % NaCl was shown by Lv and co-workers. 34 The hydrate dissociation condition of (CO 2 + cyclopentane) in the electrolyte aqueous solution of NaCl (up to 20 wt %) was reported by Ngema et al 29 They found that NaCl shifts the thermodynamic condition of hydrate formation to lower temperatures and higher pressures. Lee et al revealed that the addition of 3.5 wt % NaCl hinders the capture of CO 2 into the hydrate phase.…”
Section: Introductionmentioning
confidence: 85%
“…Cha et al suggested that cyclopentane–CO 2 and cyclohexane–CO 2 binary hydrate have mild hydrate formation temperature and fast formation kinetics than CO 2 simple hydrate. Chen et al measured the phase equilibrium data and dissociation enthalpies for cyclopentane + methane + water + NaCl systems and Lv et al studied the formation kinetics of the same systems. Also, Cai et al , investigated the thermodynamics and kinetics of a CP–methane binary hydrate in fresh water and brine solutions separately.…”
Section: Introductionmentioning
confidence: 99%